Nursing care on immunosuppressive drugs administration on liver transplantation: literature review - Sasso-Mendes, Karina Dal; Silveira, Renata Cristina de Campos Pereira; Curvo, Patrícia Abrahão; Galvão, Cristina Maria (Brazilian Journal of Transplantation, 2008)
Purpose: Searching for evidences available in the literature concerning the immunosuppressive drugs administration, focusing particularly the nursing care in liver transplantation. Methods: The integrant literature review was the research method used for this study. The internet was employed in order to conduct the electronic search on the MEDLINE and CINAHL databases. The keywords employed were: immunosuppressive agents, nursing care and liver transplantation. Inclusion criteria for selection of articles included studies dealing with immunosuppressive drugs administration on liver transplantation published between 1988 and 2008, in the English, Spanish and Portuguese languages. A sample of eight scientific papers was selected. Results: In addition to drugs administration, the nurse is responsible for the results monitoring, prevention of complications, and patient education regarding the immunosuppressive intake. Cyclosporine and tacrolimus are indicated as prophylactic treatment against rejection of transplanted organs and for chronic rejection treatment. Conclusion: Drugs administration in liver transplantation is more than the sole drugs administration, but also a health education process, that allows to patients and their families the adequate implementation of a harmless in-home pharmacological therapy.